Spontaneous pneumomediastinum – a rare cause of chest pain and dyspnoe in children - Mikoś, Marcin; Jończyk-Potoczna, Katarzyna; Sobkowiak, Paulina; Bręborowicz, Anna; Nagła, Edyta; Mrówczyńska, Magdalena; Wojsyk-Banaszak, Irena (Journal of Medical Science, 2021)
Introduction. Spontaneous pneumomediastinum is a very rare condition in children. Nevertheless it should be considered in the differential diagnosis in patients who present with chest pain and dyspnoe. Aim. The aim of our study was to describe clinical presentation, management and outcomes of the paediatric patients with spontaneous pneumomediastinum Material and Methods. This was a retrospective analysis of the charts of all the patients who were admitted to the Department of Pneumonology, Paediatric Allergy and Clinical Immunology in a ten year period from 01.01.2011 till 31.12.2020 in whom spontaneous pneumomediastinum was diagnosed. Results. There were 11 children (7 females) with spontaneous pneumomediastinum. The median age of the children was 11 years (range 3 to 17.5 years). Most of the children presented to the hospital with chest pain, three children complained of the neck swelling and four children developed dyspnoe. Three children with the primary spontaneous pneumomediastinum had a history of physical exercise prior to the onset of symptoms. The secondary spontaneous pneumomediastinum occurred in two children with asthma and 4 children with pneumonia. Genetic material of human Bocavirus was identified in 3 cases. In 81.8% of children pneumomediastinum was accompanied by subcutaneous emphysema and in one case, in a child with severe pneumonia and respiratory insufficiency caused by Bocavirus with pneumorrhachis. In 10 children computed tomography was performed, bronchoscopy in 4 and esophagoscopy in two children. There was no evidence of esophageal rupture or bronchial tree rupture in any of our patients. Three children with pneumonia and pneumomediastinum developed respiratory insufficiency, two of these were treated with mechanical ventilation and one with High Flow Nasal Cannula oxygen therapy. All the children received oxygen. In one child surgical procedure was performed and the drain was inserted into mediastinal space in order to decompress it. Outcome was favourable in all children. Mean time to recovery was 10.6 ± 1.2 days. There was no recurrence of symptoms in any of our patients. Conclusions. Spontaneous pneumomediastinum in most cases is a benign condition, sporadically however it may progress rapidly, leading to respiratory insufficiency and warrant invasive management.